Bonus-Driven Repurchases - Cheng, Yingmei; Harford, Jarrad; Zhang, Tianming (Tim) (Journal of Financial and Quantitative Analysis, 2015)
Abstract Using a large hand-collected database of chief executive officer (CEO) bonus structures, we find that when a CEO’s bonus is directly tied to earnings per share (EPS), his company is more likely to conduct a buyback. This effect is especially pronounced when a company’s EPS is right below the threshold for a bonus award. Share repurchasing increases the probability the CEO receives a bonus and the magnitude of that bonus, but only when bonus pay is EPS based. Bonus-driven repurchasing firms do not exhibit positive long-run abnormal returns.